Affect, Behaviors of Children With Intellectual Disabilities and Parents' Coping Strategies During the COVID-19 Pandemic - Ma, Minjie; Wang, Xiao; Qi, Peiyu; Wang, Tingzhao (Frontiers in Psychiatry, 2022)
Background In early 2020, the COVID-19 pandemic emerged. To prevent the spread of the virus, China implemented restrictions on going out and ensured that people stayed at home. This study aims to investigate the affect and behaviors of children with intellectual disabilities (ID) during the lockdown. The informal coping strategies adopted by parents and their effects were further evaluated. Methods In this study, a total of 457 parents of children (mean age: 14.82 years ± 1.96) with ID in 12 provincial administrative regions across China were surveyed online using the Positive and Negative Affect Scale and our own questionnaire on daily behaviors, problem behaviors and informal coping strategies. Results During the COVID-19 pandemic, the positive affect (PA) score was significantly higher than that of negative affect (NA) (p < 0.001). Some children experienced mostly positive changes in sleep (16.63%), communication (14.66%), and diet (5.69%). However, more than one-third (39.39%) exhibited problem behaviors such as hyperactivity. A significant correlation was found between affect and behavior. The informal coping measures adopted by parents were generally effective among affect and the relationship with problem behaviors. Conclusions The affect of the children with ID at home was mainly positive. The overall behaviors (diet, sleep, and communication) were good, but there were problem behaviors. Effective coping strategies are associated with higher PA, lower NA, and fewer problem behaviors. The greater the number of effective coping strategies, the lesser the problem behaviors.